The Importance of Chest CT Scan in COVID-19 - Eric Daniel Tenda; Mira Yulianti; Moses Mazmur Asaf; Reyhan Eddy Yunus; Wita Septiyanti; Vally Wulani; Ceva Wicaksono Pitoyo; Cleopas Martin Rumende; Siti Setiati (Acta Medica Indonesiana)
The coronavirus disease 2019 (COVID-19) is a highly transmissible acute respiratory disease that is caused by the Severe Acute Respiratory Syndrome CoronaVirus-2 (SARS-CoV-2), a beta coronavirus first discovered in Wuhan, China, in late 2019. COVID-19 has been spreading swiftly globally, and as of March 2020, has been officially declared a pandemic by the World Health Organization (WHO). One of the challenges in managing COVID-19 is the identification of a swift, accessible, and reliable diagnostic modality that could serve as an alternative to a reverse-transcriptase polymerase chain reaction (RT-PCR). As of the writing of this paper, RT-PCR is still the recommended tool in diagnosing COVID-19, but the notion of a more prompt and accurate diagnostic tool is a possibility worth looking into. The objective of this case study is to investigate the importance and utility of chest computed tomography (CT) in the diagnosis of COVID-19, as increasing pieces of evidence suggest that chest CT could prove useful in the clinical pathway in diagnosing COVID-19.